Caractérisation Agro-Morphologique De Variétés De Cotonnier (Gossypium Hirsutum) Pour Une Régionalisation Economique Pour La Production Du Coton Au Bénin - Alexis, Hougni; Lucien, Imorou; Augustin, Dagoudo; Nouhoun, Zoumarou-Wallis (European Scientific Journal, ESJ, 2016)
To take more account of the terroir effect in varietal choice and address the concerns of cotton farmers who disapprove the agricultural policy of single variety, research on varietal regionalization was initiated during four campaigns, by the Agricultural Research Center for Cotton Fibers. This idea is reinforced by the diversity of agro-ecological zones of the country. The nonrenewal of the variety in extension since the 2002-2003 campaign is also an element of justification concerns of industry players. This study aims to exploit the terroir effect to identify the most suitable varieties for each agroecological zone and meet the needs of industry players including producers and ginners. The experiment was conducted in 2011-2012 on Angaradébou sites, Okpara, Savalou and Ketou respectively representing the zones 1 (Alibori / Atakora); 2 (Borgou / Donga); 3 (Hills) and 4 (Zou / Ouemé Plateau / Mono-Couffo). The adopted experimental device is a Fisher block with four replicate and eight treatments or varieties H 279-1 in extension witness. Other varieties include E 944-2; E 956-2; H 769-5; H 782-3; I 875-3; K 768-3 and K 787-2.The measured parameters are the earliness of production, seed cotton yield in the field, the weight of 100 seeds and the fiber ginning outturn. Data analysis revealed significant differences between and inside sites for most measured parameters. The results showed that varieties E 956-2 (1983.85 kg / ha), H 769-5 (1820.49 kg / ha), K 768-3 (1735.42 kg / ha) and H 782-3 (1533.59 kg / ha) in terms of seed cotton yield in the field and compared their performance to shattering were the best respectively in zones 1, 2, 3 and 4.